DETERMINATION OF WATER CONSUMPTION OF POTATO UNDER IRRIGATION SYSTEMS AND IRRIGATION INTERVALS BY USING POLYMERS AND BIO-FERTILIZERS IN DESERT SOILS - A. A. A. A. Al-Lami; A. S. Ati; S. S. Al-Rawi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
Two field experiments were conducted during the spring season 2020 in Karbala governorate, to study the effect of sprinkler and surface drip irrigation systems to determine water consumption of potatoes and irrigation intervals using polymers and bio-fertilizers in desert soils. The experiment included three factors: 1-Irrigation system surface drip T1 and sprinkler T2, 2- The Irrigation interval: every 2 days I1, 4 days I2 and 6 days I3, 3- Addition of soil conditioners: control without any addition C, bio-organic fertilizers (seek) B, polymer (zeba) P, and polymer+ bio-organic fertilizers P+B. The experiment was designed according to the nested design with three replicates. Potato tuber class (Hermosa) rank E was planted. The results showed that the operating pressure of 50-150 kPa was drip and sprinkler irrigation, respectively. Irrigation interval treatment I1 also obtained the lowest added water depth of 212.64 and 486.70 mm at the drip and sprinkler irrigation systems, respectively. Moreover, the actual consumptive use ETa values ​​for irrigation interval I1, I2, and I3 at drip irrigation were 276.44, 428.31, and 593.04 mm, respectively. Though at sprinkler irrigation were 550.50, 959.46, and 1385.08 mm for irrigation intervals I1, I2, and I3, respectively. The highest values ​​of crop coefficient at tuber formation and filling stage were 0.66, 0.79, 1.06, 1.86, 3.42, and 4.73 for the irrigation interval I1, I2, and I3, respectively, at the drip and sprinkler irrigation systems.